The degree of maternal nutrient restriction during late gestation influences the growth and endocrine profiles of offspring from beef cows - Lopez Valiente, Oscar Sebastian (2021)
Cow–calf operations in Argentina are managed under extensive grazing condition and the quality of forages is often poor during the second half of gestation. The severity of nutrient restriction in bovine gestation, caused by seasonal pasture production, often results in poor production traits in progeny. The objective of the current study was to determine whether different levels of maternal nutrient intake in beef cows during late gestation affect fetal and postnatal growth, glucose metabolism, and insulin-like growth factor 1 (IGF1) concentrations in offspring of beef cattle.